Keberhasilan Blok Saraf Kombinasi Femoral-Sciatic Popliteal pada Pasien Chronic Limb-Threatening Ischemia Berisiko Tinggi: Case Report - Putu Gede Ary Sanjaya; I Gusti Ngurah Mahaalit Aribawa; Tjokorda Gde Agung Senapathi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Patients with Critical Limb-Threatening Ischemia (CLTI) accompanied by sepsis and complex comorbidities such as diabetes mellitus, coronary artery disease, and metastatic malignancy are at high risk for hemodynamic instability when undergoing general anesthesia. In such clinical circumstances, regional anesthesia becomes a safer alternative, as it helps maintain cardiovascular stability, minimizes respiratory depression, and reduces exposure to systemic anesthetic agents that may further compromise organ function. a 61-year-old male with left foot CLTI classified as Rutherford V, sepsis, and hypoactive delirium underwent a below-knee amputation. The patient had significant comorbidities, including type 2 diabetes mellitus, hypertension, coronary artery disease, and papillary thyroid carcinoma with pulmonary metastases, with a functional status of 4-5 METs and ASA III. Laboratory evaluation revealed marked leukocytosis, hypoalbuminemia, hypoglycemia, primary hypothyroidism, and mild renal impairment, while echocardiography demonstrated preserved left ventricular systolic function. Considering the substantial risks associated with general anesthesia, a combined peripheral nerve block technique femoral and sciatic–popliteal was selected using 0.375% ropivacaine. The procedure proceeded uneventfully, with stable vital signs and no episodes of hypotension, desaturation, or block-related complications. Postoperatively, the patient experienced adequate pain control and maintained stable hemodynamic recovery. The use of regional anesthesia via combined femoral and sciatic–popliteal nerve blocks proved to be safe and effective for a high-risk patient with sepsis and CLTI. This approach preserved hemodynamic stability, provided optimal analgesia, and minimized the need for general anesthesia, making it a viable option for similarly complex cases.